Treponema pallidum subsp. pallidum strains DAL-1 and Philadelphia 1 differ in generation times in vitro as well as during experimental rabbit infection - Bosák, Juraj; Mikalová, Lenka; Hrala, Matěj; Pospíšilová, Petra; Faldyna, Martin; Šmajs, David (PloS one, 2024)
In this work, we determined that Treponema pallidum subsp. pallidum (TPA) DAL-1 (belonging to Nichols-like group of TPA strains) grew 1.53 (± 0.08) times faster compared to TPA Philadelphia 1 (SS14-like group) during in vitro cultivations. In longitudinal individual propagation in rabbit testes (n = 12, each TPA strain), infection with DAL-1 manifested clinical symptoms (induration, swelling, and erythema of testes) sooner than Philadelphia 1 infection, which resulted in a significantly shorter period of the experimental passages for DAL-1 (median = 15.0 and 23.5 days, respectively; p < 0.01). To minimize the confounding conditions during rabbit experiments, the growth characteristics of DAL-1 and Philadelphia 1 strains were determined during TPA co-infection of rabbit testes (n = 20, including controls). During two weeks of intratesticular co-infection, DAL-1 overgrew Philadelphia 1 in all twelve testes, regardless of inoculation ratio and dose (median of relative excess DAL-1 multiplication = 84.85×). Moreover, higher DAL-1 to Philadelphia 1 inoculum ratios appeared to increase differences in growth rates, suggesting direct competition between strains for available nutrients during co-infection. These experiments indicate important physiological differences between the two TPA strains and suggest growth differences between Nichols-like and SS14-like strains that are potentially linked to their virulence and pathogenicity.
Keywords: Syphilis; Animals; Rabbits; králíci; Treponema pallidum; mužské pohlaví; zvířata; Male; syfilis; testis; Testis